COMPARISON OF AEROBIC AND STRETCHING EXERCISE ON DYSMENORRHEA PAIN IN STUDENT AISYIYAH BANTEN - Indriyani, Iin; Rismayanti, Tetin (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Dysmenorrhea is something condition pain that occurs during _ before nor moment menstruation. Condition dysmenorrhea of course No endanger health the sufferer, however condition This give discomfort as well as can bother activity for the sufferer. There are two ways to treat dysmenorrhea handling that is non-pharmacological (exercise breathing, warm compresses, physical exercise aerobic and stretching exercises) and pharmacological (drugs). The researcher 's research method use is Quasi experimental type. Samples used as many as 50 female students health with consider criteria inclusion and exclusion. The results of the aerobic exercise test were obtained (p value 0.001) which means there is connection whereas The results of the stretching exercise test were obtained (p value 1.00) which was significant No there is connection . In conclusion exercise physique aerobic exercise capable lower intensity painful moment period whereas stretching exercise is not lower intensity painful period.